2013
DOI: 10.1159/000350185
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mechanisms and the Treatment of Motion Sickness

Abstract: The aim of this review is to provide an overview of the physiological basis, clinical picture and treatment options for motion sickness. Motion sickness is a well-known nausea and vomiting syndrome in otherwise healthy people. The physical signs of motion sickness occur in both humans and animals during travel by sea, automobile or airplane and in space. Furthermore, some other special situations, such as simulators, the cinema and video games, have been described as causing pseudomotion sickness. Children bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 78 publications
2
70
0
3
Order By: Relevance
“…This might be potentially caused by vestibular hyperexcitability in children which should be further investigated. As children aged 2 to 12 years are more susceptible to suffer from motion sickness than adults, the vestibular hyperexcitability found in this study might be brought into context with that(23, 24). Henriques for instance recently demonstrated, that children aged 9 years are most likely to be susceptible for motion sickness, whereas children older than 9 years become less susceptible the older they get (25).Furthermore, he demonstrated that there is an association between motion sickness in children and postural stability and between motion sickness in children and the children's subjective sensation of disequilibrium, which was measured with Motion Sickness Susceptibility Questionnaire Short-Form (MSSQ-short) and Dizziness Handycap Inventory (DHI) (25).…”
supporting
confidence: 61%
“…This might be potentially caused by vestibular hyperexcitability in children which should be further investigated. As children aged 2 to 12 years are more susceptible to suffer from motion sickness than adults, the vestibular hyperexcitability found in this study might be brought into context with that(23, 24). Henriques for instance recently demonstrated, that children aged 9 years are most likely to be susceptible for motion sickness, whereas children older than 9 years become less susceptible the older they get (25).Furthermore, he demonstrated that there is an association between motion sickness in children and postural stability and between motion sickness in children and the children's subjective sensation of disequilibrium, which was measured with Motion Sickness Susceptibility Questionnaire Short-Form (MSSQ-short) and Dizziness Handycap Inventory (DHI) (25).…”
supporting
confidence: 61%
“…In driving situations the inverse occurs, since PLOF is enhanced, albeit with different spatial and temporal properties (e.g., the seated frame of reference in the car and higher speeds). For example, people with fear of heights might be very sensitive to the absence of motion parallax cues, while people with fear of driving might be more sensitive to conflicts to optic flow over large portions in the visual field, without the usually simultaneous vestibular stimulation (Schmäl, 2013). It seems to be possible that people more susceptible to this conflict are more prone to fear of driving, and others less sensitive to it show hypophobia and a lack of fear of driving at high speeds.…”
Section: Drivingmentioning
confidence: 99%
“…Two main classes of drug, anticholinergics (e.g., scopolamine) and antihistamines (e.g., promethazine) are the most common treatments for motion sickness (Schmäl, 2013; Golding and Gresty, 2015). However, these types of agents are variably efficacious in motion sickness and are associated with unwanted side effects including sedation, drowsiness, blurred vision, depression, and dry mouth/nose/throat (Spinks and Wasiak, 2011; Schmäl, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these types of agents are variably efficacious in motion sickness and are associated with unwanted side effects including sedation, drowsiness, blurred vision, depression, and dry mouth/nose/throat (Spinks and Wasiak, 2011; Schmäl, 2013). Furthermore, the efficacy of all existing anti-motion sickness drugs is quite modest.…”
Section: Introductionmentioning
confidence: 99%